Badminton Long-serve Skill’s Level of Physical Education Male Students in the Universitas Islam Riau - Gazali, Novri; Cendra, Romi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
This study was aimed to determine the skill level of the student badminton long service Penjaskesrek Riau Islamic University. Type of this research is quantitative descriptive research. The population in this research is a student of Penjaskesrek Riau Islamic University year of active 2015/2016 generation force totalling 236 overall students from 8 class. While the samples taken in this study are male students who numbered 40 people. Sampling techniques in the study using a purposive sampling technique, namely by taking a sample based on certain considerations. The instruments used in this study is a long service badminton service test of Nurhasan. Data analysis method used is descriptive statistics, statistics is intended for gathering data, presenting data and specify a value. The results of research is poured into 5 categories that is very good, good, enough, less and less once. Based on the data analysis that has been done, the result shows that it can be concluded that this research is the level of long service skill of students of Penjaskesrek Islamic University of Riau category enough, that is 16 students with percentage of 40% from 40 students.